Influencing characteristics of short-time aerobic digestion on spatial distribution and adsorption capacity of extracellular polymeric substances in waste activated sludge. Issue 56 (18th September 2018) - Liu, Ying; Lv, Wenzhou; Zhang, Zhiqiang; Xia, Siqing
Abstract : The spatial distribution and adsorption capacity of extracellular polymeric substances (EPS) were systematically investigated for waste activated sludge (WAS) treated by a short-time aerobic digestion (STAD) process. Abstract : The spatial distribution and adsorption capacity of extracellular polymeric substances (EPS) were systematically investigated for waste activated sludge (WAS) treated by a short-time aerobic digestion (STAD) process. During the STAD process, both the slime and the loosely bound EPS (LB-EPS) increased first and then decreased, while the tightly bound EPS (TB-EPS) gradually increased all the way. The variations of the fluorescence intensities at peaks A and B for the slime, the LB-EPS and the TB-EPS were consistent with the above variation of their concentrations. In the initial stage of the STAD process, aeration scour was mainly responsible for the release of LB-EPS and TB-EPS, which further resulted in the increase of slime and LB-EPS. Meanwhile, newly secreted EPS by microorganisms led to the increase of TB-EPS. In the later stage of the STAD process, the biodegradation of soluble organic matter caused the concentration decrease of both slime and LB-EPS. The Pb 2+ adsorption capacity by LB-EPS, TB-EPS and total EPS gradually increased with the increasing of STAD time, suggesting that the LB-EPS and TB-EPS played a key role in the adsorption of Pb 2+ and the LB-EPS had a higher adsorption capacity. FTIR results further indicated that STAD could improve the amounts of functional groups, especially for –OH, –COOH and –NH2 in both LB-EPS and TB-EPS responsible for the binding of heavy metals, resulting in the increased adsorption capacity of EPS. Disclosing the influencing characteristics of the STAD process on the spatial distribution and the adsorption capacity of EPS in WAS for the first time, this work lays a foundation for the application of the STAD process in the reuse of WAS.